Fractionation and Antibacterial Activity of the Methanol Extract of White Champaka Flowers (Magnolia alba (DC.) Figlar) - Ulil Amna; Irma Setia Fitri; Halimatussakdiah Halimatussakdiah; Mastura Mastura; Syarifah Yanti Astryna (Biology, Medicine, & Natural Product Chemistry, 2026)
Research on fractionation and antibacterial activity test of methanol extract of cempaka putih (Magnolia alba (DC.) Figlar) flower was conducted. This study aimed to investigate the class of chemical compounds contained in the methanol extract of cempaka putih (M. alba (DC.) Figlar) flowers and to test the antibacterial activity of the methanol extract of M. alba (DC.) Figlar flowers against Staphylococcus aureus and Escherichia coli bacteria. Based on the results of phytochemical screening, these showed that the methanol extract and its fractions contained secondary metabolites of alkaloid, terpenoids, steroids, saponins, flavonoids, phenols and tannins. Testing for antibacterial activity was carried out by the Kirby-Bauer method (agar diffusion) against S. aureus and E. coli bacteria, at concentrations of 5, 10, 20 and 40 ppm. The antibacterial activity test showed that the methanol extract gave moderate activity against E. coli and fraction A gave moderate activity against S. aureus. While other fractions showed weak activities against both bacteria.